A Perspective of Theory of Planned Behavior and Attribution Theory for PBB P2 Taxpayer Compliance in Probolinggo - Sulistianingtyas, Veronica; Rosidi, Rosidi; Subekti, Imam (Universitas Negeri Malang, 2018)
This study aims to show that attitude to comply, subjective norms, and perceived behavioral control had affect the intent to obey. Furthermore, perceived behavioral control and intention to abide affect on PBB tax compliance refers to the Theory of Planned Behavior. This study also adds a variable: the sanctions, that refers to Attribution Theory which predicted to affect PBB taxpayer compliance behavior. The sample was PBB taxpayers who have tax object in Probolinggo. The results showed that the attitude to obey had positive influence on the intention to comply, subjective norms had negatively affected on the intention to obey and perceived behavioral control had positive influence on the intention to obey. Moreover, these results also prove empirically that the intention to obey and perceived behavioral control had positive effect on PBB tax compliance, while the sanctions have no effect on PBB tax compliance. In addition, the intention to obey have the effect of partial mediation on relationships perceived behavioral control and PBB taxpayer compliance.